Age‐related changes in gait speeds and asymmetry during circular gait and straight‐line gait in older individuals aged 60–79 years. Issue 5 (29th March 2021) - Hirono, Tetsuya; Ikezoe, Tome; Yamagata, Momoko; Kato, Takehiro; Umehara, Jun; Yanase, Ko; Nakao, Sayaka; Tsuboyama, Tadao; Tabara, Yasuharu; Matsuda, Fumihiko; Ichihashi, Noriaki; ,
Abstract : Aim: The present study aimed to investigate the age‐related changes in gait speeds and asymmetry during circular and straight‐line gaits among older adults aged 60–79 years. Methods: The study included 391 community‐dwelling older adults aged >60 years, who participated in the Nagahama cohort study. They were assigned to four age groups: 60–64 years (early 60s), 65–69 years (late 60s), 70–74 years (early 70s) and 75–79 years (late 70s). For the circular gait test, the time required to walk twice around a 1‐m diameter circle for right and left rotations were measured. The average time of the two trials was measured as the circular gait time, and the side‐to‐side difference in the circular gait times was calculated as an asymmetry index. Walking speed, asymmetry of step length, and asymmetry of stance duration time during straight‐line gait at comfortable and maximal walking pace were measured. Results: Circular gait time in older women in the late 70s group was significantly slower than that in other age groups; however, no age‐related change was observed in older men. Maximal gait speeds in the early and late 70s groups were significantly slower than those in the early 60s group. Conclusions: Age‐related decline in circular gait speed was observed in older women aged ≥75 years, but not in older men. Maximal straight‐line gait speed decreased significantly in both genders after the age of 70 years. Geriatr Gerontol Int 2021; 21: 404–410 .